TO DIE AND LET DIE: A JUST THEOLOGY OF CEDING SPACE - T. Van Wyk (Acta Theologica)
Over the past few years, there has been a significant intellectual and artistic emphasis on the manner in which one considers or approaches the end of life. This is in conjunction with a renewed ethical discussion about choosing the manner and time of one’s death in light of a diminished quality of life. Large populations across the world are ageing, presenting unique challenges to healthcare and civic infrastructure. The planet is suffering because of a climate crisis, due to the overburdening of resources. In light of all this, it is argued in this contribution that a renewed theological consideration of death is necessary. In his theology about the Trinity, Jürgen Moltmann makes a remark about his understanding of the perichoretic unity of the persons of the Trinity, in which the persons of the Trinity “cede” space for one another. Ceding space creates space (room) for authentic existence. This contribution considers and utilises Trinitarian “spatial” theology as foundation for rethinking the complexity and balance of life and death. It is ultimately argued that “creating space for death” could serve as a foundation for an ethical framework for decision-making, as well as foster a compassionate community that provides space for each other’s diversity – in life and in death.